2002
DOI: 10.1080/09638280110066299
|View full text |Cite
|
Sign up to set email alerts
|

Understanding return to work behaviours: promoting the importance of individual perceptions in the study of return to work

Abstract: Insights into an individual's perceptions of their impairment and the personal relevance of work can promote a better understanding of return to work behaviour. Integrating individual perceptions is essential to advancing a multidimensional approach in return to work research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 13 publications
3
36
1
Order By: Relevance
“…The idiographic analysis also revealed distinctive issues in the lifeworlds of each participant that influenced return to work, supporting previous research that demonstrates both personal and environmental factors as jointly influencing this process [33].…”
Section: Critical Evaluationsupporting
confidence: 57%
“…The idiographic analysis also revealed distinctive issues in the lifeworlds of each participant that influenced return to work, supporting previous research that demonstrates both personal and environmental factors as jointly influencing this process [33].…”
Section: Critical Evaluationsupporting
confidence: 57%
“…Sampaio 31 argues that absenteeism reinforces in the workers the extent of their disability, especially by the loss of the social role derived from their work. The workers corroborated the evidence that RTW success does not necessarily imply full recovery from injury 12 . The perception of pain, grip strength and functional disability in particular improved over the first months after the return to occupational activities.…”
Section: Discussionsupporting
confidence: 70%
“…External factors such as domestic environment, leisure and social support can act as facilitators or barriers to work participation 10 . Psychological and clinical characteristics, economic aspects and workplace organizational, psychosocial and physical factors are being associated with RTW 9,11,12 . However, it is not yet possible to accurately predict which workers with recent hand trauma will develop a chronic disability.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limited research, the severity of stroke sequelae frequently has been shown to modulate return to work, with more severe impairments reducing the chance that the stroke survivor will return to work 486,[491][492][493][494] ; accordingly, amelioration of these impairments with the rehabilitation methods discussed in previous sections of the present statement might facilitate vocational reintegration. However, Shaw and colleagues 495 found that individuals' perception of their impairment level was key to returning to work, and thus, it may be that absolute impairment is less important than stroke survivors' beliefs in their abilities (ie, a personal factor within the ICF model). Koch and colleagues 490 found that the individuals who returned to work in their study demonstrated greater patience, determination, and sense of humor than individuals who did not.…”
Section: Return To Workmentioning
confidence: 99%